Study on the whole lifecycle energy consumption scenarios of expressway - Peiqiang Cui; Qi Yu; Jie Liu; Ning Mao; Yizheng Wu (Science and Technology for Energy Transition)
This paper constructs a set of energy consumption scenarios for typical expressway construction, operation and maintenance phases, and analyses the energy demand under each scenario. Firstly, a comprehensive lifecycle energy consumption framework for expressway is established, detailing the energy consumption scenarios during construction, operation, and maintenance phases. Secondly, based on literature review and scenario assumptions, the study examines the energy consumption levels under different scenarios and analyses the proportion of energy consumption in each scenario. The results show that the ratio of energy consumption during the construction, operation and maintenance phases of expressway is about 5:10:3. The energy consumption during the construction phase is the highest for the construction of expressway trunk lines, accounting for about 80.6% of the total energy consumption. During the operation phase, fuelling and refuelling stations consume the most energy, accounting for about 71.4%. The energy consumption of expressway trunk lines is the highest during maintenance phase, which accounting for about 70%. This analysis facilitates a deeper understanding of the characteristics of the integration between transportation and energy networks, and assists the transportation sector in achieving carbon peak and carbon neutrality goals in a scientifically sound manner.